2021
DOI: 10.1096/fj.202100121rrr
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin‐1 increases glycolysis in pancreatic cancer cells and triggers cachectic states

Abstract: In pancreatic cancer, autocrine insulin-like growth factor-1 (IGF-1) and paracrine insulin stimulate both IGF-1 receptor (IGF1R) and insulin receptor (IR) to increase tumor growth and glycolysis. In pancreatic cancer patients, cancer-induced glycolysis increases hepatic gluconeogenesis, skeletal muscle proteolysis, and fat lipolysis and, thereby, causes cancer cachexia. As a protein coexisting with IGF1R and IR, caveolin-1 (cav-1) may be involved in pancreatic cancer-induced cachexia. We undertook the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 40 publications
5
31
0
Order By: Relevance
“…For example, long noncoding RNA SNHG11 facilitates prostate cancer progression by upregulating IGF1R expression 27 . IGF1R increases the proliferation and glycolysis of pancreatic cancer 28 . HOXB13 accelerates gastric cancer cell migration and invasion by upregulating the expression of IGF1R 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, long noncoding RNA SNHG11 facilitates prostate cancer progression by upregulating IGF1R expression 27 . IGF1R increases the proliferation and glycolysis of pancreatic cancer 28 . HOXB13 accelerates gastric cancer cell migration and invasion by upregulating the expression of IGF1R 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 27 IGF1R increases the proliferation and glycolysis of pancreatic cancer. 28 HOXB13 accelerates gastric cancer cell migration and invasion by upregulating the expression of IGF1R. 29 IGF1R is activated through miR‐122 downregulation, resulting in activation of the RAS/RAF/ERK pathway in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolin-1 (CAV-1) plays an important role in regulating lipid metabolism. Hu et al [ 163 ] revealed that CAV-1 levels in tumor grafts are correlated with the expression levels of the enzymes that regulate lipolysis. TGF-β deficiency can increase stromal autophagy and the generation of ketone bodies.…”
Section: Tgf-β-dependent Metabolism Of Stromal–epithelial Coupling An...mentioning
confidence: 99%
“…8486 Table 2 summarizes the mechanism of cachexia. 13,14,34,87124 The broad picture of CC is summarized in Figure 1.…”
Section: Imbalance Of Anabolism and Catabolism: Insight Into The Mole...mentioning
confidence: 99%